1983
DOI: 10.1508/cytologia.48.343
|View full text |Cite
|
Sign up to set email alerts
|

Cytological effects of medicinal plants in Qatar III. Mitotic effect of water extract of Anastatica hierochuntica L. on Allium cepa.

Abstract: The cytological, antifungal and antimicrobial effects of plant extracts, especially those having medicinal importance, attracted the attention of many investigators, Ohno (1960), noxious plants, Singh and Madhu (1978) studying the antifungal pro perties of 34 flowering plants and Shehab et al. (1978), reporting the cytological effects of water extracts of Achillea fragrantissima.This work represents part III in the survey concerning the cytological effects of medicinal plants growing in Qatar.The water extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Also Shalaby et al (1986) reported the same trend where MI changes were not correlated with changes in DNA content in Vicia faba root tip cells treated with growth regulators under different salininty conditions. Changes in mitotic activity were recorded and discussed by some authors as Shehab andAdam (1981, 1983), Lazar and Keul (1983), Adam and Rashad (1984) and Amer et al (1987 Concerning the percentages of the different mitotic phases Table 3 shows that the general effect of malathion and tamaron in increasing the percentage of metaphase and ana-telaphase was accompanied by a rise in protein content of the treated root tips (Table 2). This may be explained on the basis that spindle formation required active protein synthesis to form the microtubules (spindle sub-units).…”
Section: Resultsmentioning
confidence: 98%
“…Also Shalaby et al (1986) reported the same trend where MI changes were not correlated with changes in DNA content in Vicia faba root tip cells treated with growth regulators under different salininty conditions. Changes in mitotic activity were recorded and discussed by some authors as Shehab andAdam (1981, 1983), Lazar and Keul (1983), Adam and Rashad (1984) and Amer et al (1987 Concerning the percentages of the different mitotic phases Table 3 shows that the general effect of malathion and tamaron in increasing the percentage of metaphase and ana-telaphase was accompanied by a rise in protein content of the treated root tips (Table 2). This may be explained on the basis that spindle formation required active protein synthesis to form the microtubules (spindle sub-units).…”
Section: Resultsmentioning
confidence: 98%
“…In an earlier study, sulforaphne was confirmed to inhibit extracellular, intracellular and antibiotic resistant strains of Heliocobacter pylori and prevented against benzo[a]pyrene induced stomach tumors [65,70]. Many individual flavonoids such as quercetin, rutin, kaempferol, flavones glycoside, and hypolaetin 8-glucoside, and other A. hierchuntica chemical constituents, have been reported to possess gastric protective effects [69,[86][87][88][89][90]. Similarly, saponins were also reported to have antiulcer effects in rats [85].…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, the results of the preliminary toxicity studies in Brine shrimp lethality test were found to be useful in initial assessment of chemicals and plant extracts for detailed toxicology and pharmacology investigations [19,34]. In an earlier experiment, A. hierochuntica extract treatment induced some mitotic index depression in Allium cepa meristems [11]. The cytotoxicity shown by A. hierochuntica ethanol extract in the present study successfully indicated the need for detailed investigations on the effects of acute and chronic treatment using different official experimental models [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). A. hierochuntica L. (Family: Brassicaceae) is known as Kaff-e Maryam in Saudi Arabia and other Arab countries, where it is widely consumed as a tea beverage and to treatment of many conditions, such as difficult childbirth, blood pressure, diabetes mellitus and uterine hemorrhage (Khalifa and Ahmad, 1980;El-Ghazali et al, 2010;Jaradat, 2005;Sehab et al, 1983;Bellakhdar et al, 1991;Batanouny 1999;Eman et al, 2011;Daur 2012).…”
Section: Introductionmentioning
confidence: 99%